DESIGN AND OPTIMIZATION OF A WATER COOLED ANTENNA FOR MICROWAVE ABLATION USING FINITE ELEMENT METHOD - Adeneye, S. O.; Akpochafor M.O, Ibitoye Z.A; Ajekigbe A.T, Aweda M.A (UNILAG Journal of Medicine, Science and Technology, 2019)
Microwave ablation is a technique for treating cancerous tissues with the application of heat. Some tumors are located such that they cannot be successfully treated with conventional external radiation beam techniques. Microwave ablation is currently an alternative option being considered for the treatment of unresectable tumors. In this study, we designed a water cooled microwave antenna for tumor ablation. The water cooled antenna for hepatic microwave ablation was designed using Finite Element Methods (FEMs) (COMSOL MULTIPHYSICSTM version 4.4). Finite element methods were used to study the electromagnetic (EM) field and thermal distributions in liver. The water slot position, water slot length and the antenna slot length, from the tip of the antenna (z = 0 mm) were varied within the ranges (43 ? z ? 60 mm), (1 ? z ?10.5 mm) and (1 ? z ? 20 mm) at 1 mm, 0.5 mm and 0.5 mm interval respectively, at a frequency of 2.45 GHz. The design has reflection coefficient of -25.5dB, with 94.0% power dissipation into the tissue. Experimental validation shows that the inclusion of a cooling unit reduces the backward heating and increases the power deposition into liver tissue